48 Effective atrial conducting size does not predict human af vulnerability. (5th October 2017) - O'Neill, L; Williams, S; Sohns, C; Metzner, A; Reissman, B; Whitaker, J; Mukherjee, R; Harrison, J; Wright, M; Neiderer, S; O'Neill, M
Abstract : Background: The multiple wavelet hypothesis is an established theory to explain initiation and maintenance of atrial fibrillation (AF). Purpose: We hypothesised that if the multiple wavelet hypothesis is valid for human AF, the ability of a chamber to support AF would be proportional to the Effective Atrial Conducting Size, a function of total area, conduction velocity and atrial refractoriness. Methods: High density activation mapping (CS pacing) followed by complete wide area encirclement was performed in 27 patients (19 paroxysmal, 8 persistent) undergoing 1st time ablation. The following parameters were measured: (1) LA body area [A], was measured using Carto3; (2) Refractoriness [ERP] was measured at the posterior wall; (3) Total activation time [TAT] was measured from earliest to latest LA activation; (4) Conduction velocity [CV] was defined as sqrt(A)/TAT. Effective Atrial Conducting Size was calculated as A/(CV*ERP). A rigorous AF induction protocol consisting sensed doubles, sensed triples and incremental atrial pacing was applied. Sustained AF was defined as AF >30 s duration. Results: Sustained AF was induced in 7 (26%) patients. Individually there were no differences in LA area, TAT, CV or ERP between patients with and without AF induction (all P>0.05, Figure 1). Effective Atrial Conducting Size was 3.2±0.8 m in patients in whom AF was induced, and 3.2 ±1.1 m in patients in whom AF was not induced (P=0.85). Conclusion: Effective Atrial Conducting Size was not associated with the ability to induce AF. These data suggest that multiple wavelets are unlikely to constitute the dominant mechanism of AF in these patients.